2021
DOI: 10.48550/arxiv.2108.12297
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Yau-Tian-Donaldson correspondence on a class of toric fibrations

Abstract: We established a Yau-Tian-Donaldson type correspondence, expressed in terms of a single Delzant polytope, concerning the existence of extremal Kähler metrics on a large class of toric fibrations, introduced by Apostolov-Calderbank-Gauduchon-Tonnesen-Friedman and called semi-simple principal toric fibrations. We use that an extremal metric on the total space corresponds to a weighted constant scalar curvature Kähler metric (in the sense of Lahdili) on the corresponding toric fiber in order to obtain an equivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 56 publications
(210 reference statements)
0
14
0
Order By: Relevance
“…Actually, thanks to our Corollary 2.11, we recover the result of Han Lie [22] without the need of special test configuration, see Corollary 3.13. • Finally, as we shall explain in the next sections, the converse of Theorem 3.2 was proven by the second author for weights corresponding to extremal Kähler metrics on semisimple principal toric fibrations [17].…”
Section: Definition 31 (Weighted Csck Metrics)mentioning
confidence: 84%
See 3 more Smart Citations
“…Actually, thanks to our Corollary 2.11, we recover the result of Han Lie [22] without the need of special test configuration, see Corollary 3.13. • Finally, as we shall explain in the next sections, the converse of Theorem 3.2 was proven by the second author for weights corresponding to extremal Kähler metrics on semisimple principal toric fibrations [17].…”
Section: Definition 31 (Weighted Csck Metrics)mentioning
confidence: 84%
“…Weighted cscK toric manifolds. The results from Section 2 are motivated by the study of the existence of weighted cscK metrics on toric manifolds, as studied in [17].…”
Section: Geometric Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The appendix of [13] by Yuji Odaka showed that for non-singular spherical varieties, G-uniform K-stability is equivalent to existence of cscK metrics. Jubert (see [25]) showed the equivalence between the existence of extremal Kähler metrics on the total space of semi-simple principal toric fibrations and weighted uniform K-stability of the corresponding Delzant polytopes.…”
Section: Introductionmentioning
confidence: 99%